2016
DOI: 10.1111/tid.12606
|View full text |Cite
|
Sign up to set email alerts
|

The impact of directly acting antivirals on the enzymatic liver function of liver transplant recipients with recurrent hepatitis C

Abstract: Antiviral treatment with DAAs enabled sustained elimination of recurrent HCV in liver transplant recipients and was associated with a significant improvement of the enzymatic liver function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 30 publications
2
20
1
Order By: Relevance
“…A retrospective cohort study in 52 LT patients treated with DAAs found significant decreases in serum TAC concentrations after achieving SVR . In a study examining the impact of DAAs on the enzymatic liver function of 21 LT recipients, TAC concentration‐to‐dose ratio significantly decreased stepwise from the start of treatment until week 12 of therapy, indicating increased TAC metabolism during and after treatment . Similarly, in a retrospective review of 34 simultaneous liver/kidney transplant recipients with HCV, immunosuppression dosage increases were required in seven patients during DAA treatment and five patients following treatment .…”
Section: Discussioncontrasting
confidence: 57%
See 4 more Smart Citations
“…A retrospective cohort study in 52 LT patients treated with DAAs found significant decreases in serum TAC concentrations after achieving SVR . In a study examining the impact of DAAs on the enzymatic liver function of 21 LT recipients, TAC concentration‐to‐dose ratio significantly decreased stepwise from the start of treatment until week 12 of therapy, indicating increased TAC metabolism during and after treatment . Similarly, in a retrospective review of 34 simultaneous liver/kidney transplant recipients with HCV, immunosuppression dosage increases were required in seven patients during DAA treatment and five patients following treatment .…”
Section: Discussioncontrasting
confidence: 57%
“…After week 4, the TAC dose‐normalized concentration stabilized. These results conflict with those of Raschzok et al who found the decrease most notably between week 12 of DAA and post‐week 12. Kugelmas et al saw the greatest decrease in immunosuppression at months 2 and 6 of therapy in patients treated with IFN‐based regimens.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations